Pengaruh Label Halal Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Skincare Ms Glow Pada Agen Ms Glow Di Kabupaten Sorong - Ruliyana Ruliyana; Bambang Sunatar; Karfin Karfin (Prodi Ekonomi Syariah IAIN Sorong, 2022)
This study aims to analyze the effect of halal labels and Electronic Word of Mouth on purchasing decisions for MS Glow skin care products. This study uses a correlational or associative approach with a descriptive quantitative research type. The sample in this study were 30 respondents who bought and used MS Glow skincare products. The technique taken in this study is non-probability sampling with purposive sampling type, while the data collection is carried out using a questionnaire with a closed statement type. To answer the problem and test the hypothesis, SPSS Version 28 technical analysis is used. The results showed that: first, the halal label variable (X1) had a significant effect on the purchasing decision variable (Y). Second, the Electronic Word of Mouth (X2) variable has no significant effect on the purchasing decision variable (Y). Third, the halal label variable (X1) and the Electronic Word of Mouth (X2) have a significant effect on the dependent variable, namely the purchase decision variable (Y). This study aims to analyze the effect of halal labels and Electronic Word of Mouth on purchasing decisions for MS Glow skin care products. This study uses a correlational or associative approach with a descriptive quantitative research type. The sample in this study were 30 respondents who bought and used MS Glow skincare products. The technique taken in this study is non-probability sampling with purposive sampling type, while the data collection is carried out using a questionnaire with a closed statement type. To answer the problem and test the hypothesis, SPSS Version 28 technical analysis is used. The results showed that: first, the halal label variable (X1) had a significant effect on the purchasing decision variable (Y). Second, the Electronic Word of Mouth (X2) variable has no significant effect on the purchasing decision variable (Y). Third, the halal label variable (X1) and the Electronic Word of Mouth (X2) have a significant effect on the dependent variable, namely the purchase decision variable (Y).